Impact of Economic Life on the Poetry of Ali bin Al-Jahm During the Reign of Al-Mutawakkil - Hasan, Raeed Hazim (Journal of Tikrit University for Humanities, 2024)
Economic life had a great impact on the poetry of the poets of the Abbasid state, and among these poets was the poetry of the poet Ali bin Al-Jahm during the era of Jaafar Al-Mutawakkil. Ibn al-Jahm was chosen for two main reasons: the first is due to the stylistic characteristic that distinguished his poems, which is the striking pictorial character that represented a phenomenon in his poetry, and he was one of the distinguished in it. The second is represented by his influence by the aspects of economic life in his reign, whether materialistic, such as: ways of living, methods of earning, resources and the treasury of that era, and the luxury of the caliphate, and he is one of the poets committed to his poetry